2021
DOI: 10.1038/s41467-021-21011-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of risk in autoimmune pulmonary alveolar proteinosis

Abstract: Pulmonary alveolar proteinosis (PAP) is a devastating lung disease caused by abnormal surfactant homeostasis, with a prevalence of 6–7 cases per million population worldwide. While mutations causing hereditary PAP have been reported, the genetic basis contributing to autoimmune PAP (aPAP) has not been thoroughly investigated. Here, we conducted a genome-wide association study of aPAP in 198 patients and 395 control participants of Japanese ancestry. The common genetic variant, rs138024423 at 6p21, in the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 45 publications
4
21
0
Order By: Relevance
“…It will also be important to determine the distribution of auto-Abs against other cytokines in the general population. The East Asian predominance of auto-Abs against type II IFN reflects the higher frequency of predisposing HLA-DRB1 alleles in these populations ( Chi et al, 2013 ; Ku et al, 2016 ; Pithukpakorn et al, 2015 ), raising questions about possible HLA associations for other anti-cytokine auto-Abs, as suggested for anti–GM-CSF auto-Abs in PAP patients of Japanese ancestry ( Sakaue et al, 2021 ). Another fundamental question is the nature of the cytokine-specific Igs and their B cell epitopes, which are known only for auto-Abs against type II IFN ( Lin et al, 2016 ) and IL-6 ( Nanki et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will also be important to determine the distribution of auto-Abs against other cytokines in the general population. The East Asian predominance of auto-Abs against type II IFN reflects the higher frequency of predisposing HLA-DRB1 alleles in these populations ( Chi et al, 2013 ; Ku et al, 2016 ; Pithukpakorn et al, 2015 ), raising questions about possible HLA associations for other anti-cytokine auto-Abs, as suggested for anti–GM-CSF auto-Abs in PAP patients of Japanese ancestry ( Sakaue et al, 2021 ). Another fundamental question is the nature of the cytokine-specific Igs and their B cell epitopes, which are known only for auto-Abs against type II IFN ( Lin et al, 2016 ) and IL-6 ( Nanki et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients were male (72%) and of various ancestries. A recent genome-wide association study of autoimmune PAP in patients and controls of Japanese ancestry found that the HLA class II allele HLA-DRB1*08:03, which is common in Asian populations (e.g., 8.3% in Japanese individuals) but very rare or absent in other populations, including Europeans (e.g., 0.3% in Germans, 0% in Italians), was associated (P = 0.035) with high levels of anti–GM-CSF auto-Abs in patients, suggesting an underlying genetic predisposition for the production of these auto-Abs, at least in individuals of Asian ancestry ( Sakaue et al, 2021 ). In contrast, no HLA allele was associated with these auto-Abs in a study of 47 European patients with PAP ( Anderson et al, 2019 ).…”
Section: Neutralizing Auto-abs Against Gm-csfmentioning
confidence: 99%
“…We performed GWAS genotyping of the 2,520 COVID-19 cases and 3,341 controls using Infinium Asian Screening Array (Illumina, CA, USA). We applied stringent QC filters to the samples (sample call rate < 0.97, excess heterozygosity of genotypes > mean + 3SD, related samples with PI_HAT > 0.175, or outlier samples from East Asian clusters in principal component analysis with 1000 Genomes Project samples), and variants (variant call rate < 0.99, significant call rate differences between cases and controls with P < 5.0 × 10 -8 , deviation from Hardy-Weinberg equilibrium with P < 1.0 × 10 -6 , or minor allele count < 5), as described elsewhere 48 . Details of the QC for the mitochondrial variants are described elsewhere 21 .…”
Section: Methodsmentioning
confidence: 99%
“…A genetic predisposition to the appearance of anti-GM-CSF antibodies has long been suspected; genetic studies have provided con icting results depending on ethnicity or techniques used so far. [21,22]. Serum anti-GM-CSF autoantibody levels, unlike levels in bronchoalveolar uid, do not correlate with disease severity in patients with aPAP [23,24].…”
Section: Discussionmentioning
confidence: 95%